Walk to the Beat: A Case Report of the Use of a Novel Haptic Device to Improve Walking after Stroke - Rachel C Stockley; Glenis Donaldson; Theo Georgiou; Simon Holland; Janet Van der Linden; Josie Tetley; Linda Garbutt; Ornella Pinzone (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
Background: Stroke affects 15 million people worldwide every year and leaves two-thirds of survivors with significant mobility deficits including reduced walking speed, increased unevenness of step length and asymmetry. Haptic cues, which utilise sensory stimulation and so are unaffected by visual or auditory interference could discreetly improve the gait of people after stroke. Therefore, the objective of this single mixed methods case study was to evaluate the use of a novel haptic device in a single participant after stroke. Context and purpose: After initial familiarisation, gait symmetry, walking speed and cadence of a 69 year old male stroke survivor were recorded using a Qualisys Motion Capture system whilst he walked on a ten metre walkway, firstly without and then with a haptic device on each leg, which provided a metronomic rhythmical vibratory cue. The participant then provided a user evaluation of the devices using a semi structured interview.  Results: The haptic device was evaluated positively by the participant although he noted it needed to be refined to increase its wear-ability and acceptability for everyday use. Whilst gait speed and cadence remained unaltered, there was a 14% improvement in temporal gait symmetry when wearing the haptic device, suggesting it improved this aspect of gait.  Conclusion: Whilst limited by its design, the findings of this single case study indicate that the haptic device could be a novel technology-based therapeutic adjunct to improve gait symmetry after stroke. It also provides key understanding of user needs which can be used to guide the development of a new prototype device for stroke survivors. Brief summary: Many stroke survivors have residual mobility problems. Haptic cueing may improve walking by providing a tactile cue that the participant follows to improve symmetry. This single case study suggests that gait symmetry could be improved by haptic cueing and indicates factors affecting the wear ability of such a device.